The mass-metallicity-kinematics relation of the stellar components of EAGLE galaxies - Zenocratti, Lucas Jesús (2021)
In this work, we study the stellar mass -- stellar metallicity relation as a function of the morpho-kinematics of galaxies in {\sc{eagle}} cosmological simulations. According to our findings, at a given stellar mass ($M_\star$), stellar metallicity shows a secondary dependence on the morpho-kinematics of galaxies, which is more evident towards high masses. At the high-mass end ($M_\star \gtrsim 10^{10}~\rm{M}_\odot$), dispersion-supported systems show lower metallicities, on average. In addition, low-mass galaxies with higher rotational support are somewhat more metal-poor. More massive galaxies tend to exhibit flatter morphologies, being prolate systems less metal-enriched, on average. As the redshift $z$ increases, those aforementioned dependences of metallicity on kinematics and morphology tend to become stronger at high masses. These trends are consistent with the dependences of the stellar mass -- gas-phase metallicity relation on gas fraction, star formation rate and stellar age, and the relation of the latter quantities with galaxy morpho-kinematics.